Gods of the runes : the divine shapers of fate - Joseph, Frank (Rochester, Vt. : Bear & Co., 2010)
'The ancient origins and divinatory power of the runes'--Provided by publisher.
Includes bibliographical references (p. 180-182) and index.
Keywords: Runes -- Miscellanea; Gods, Norse -- Miscellanea; Divination